Money, capital mobility, and trade : essays in honor of Robert A. Mundell - Mundell, Robert A.; Calvo, Guillermo A.; Dornbusch, Rudiger; Obstfeld, Maurice (MIT Press, 2001)
Annotation Written by Robert Mundell's academic descendants, as well as other leading economists and scholars, the essays in this volume reflect Mundell's broad influence on modern open-economy macroeconomics. The topics include the vicissitudes of gold in the international system, choice of exchange rate regime, post-World War II European monetary reform, banking crises in emerging markets, speculative attacks on fixed exchange rates, monetary policy rules, interactions between economists and policy makers over macrostabilization and structural microeconomic issues, the connection between international factor mobility and trade, the Mundell-Fleming open-economy macro model, the quantitative implications of general-equilibrium sticky price models, the international roles of the euro and yen, and the employment effects of import tariffs.